Synthesis and luminescence of binuclear lanthanide complexes with 4, 6-bis(diphenylphosphino)pyrimidine dioxide as a bridging ligand. (1st February 2023) - Bryleva, Yuliya A.; Yzhikova, Karina M.; Artem'ev, Alexander V.; Davydova, Maria P.; Rakhmanova, Mariana I.; Polyakova, Evgenia V.; Glinskaya, Ludmila A.; Samsonenko, Denis G.
Graphical abstract: Five novel binuclear Ln(III) complexes based on 4, 6-bis(diphenylphosphino)pyrimidine dioxide as well as their Eu/Tb mixed-metal complexes were synthesized and fully characterized. Energy transfer from Tb 3+ to Eu 3+ was observed for the mixed-metal complexes, which allowed us to obtain luminophores with tunable emission color from green to yellow and red. Abstract: Five new isostructural binuclear complexes [Ln2 L2 (H2 O)2 (NO3 )6 ] (Ln = Sm, Eu, Gd, Tb, and Dy) based on 4, 6-bis(diphenylphosphino)pyrimidine dioxide (L) have been synthesized, and their luminescence properties have been studied. The complexes consist of two nine-coordinated Ln(III) atoms linked by two L ligands in the O, O ´-bridging manner. The Gd 3+ complex possesses ligand-centered emission, while its Tb 3+ and Eu 3+ analogs exhibit metal-centered phosphorescence only. At the same time, the Sm 3+ and Dy 3+ complexes show both metal- and ligand-centered emission. In the complexes studied, the ligand L sensitizes the Tb 3+ emission most effectively due to the relatively high triplet energy level (23900 cm −1 ). Moreover, mixed-metal complexes [Tb2x Eu2(1-x) L2 (H2 O)2 (NO3 )6 ] (x = 0.9, 0.8, 0.6, 0.4, 0.2) have been synthesized, whose emission color can be tuned from green to yellow and red through adjusting of the Tb/Eu ratio.